A new approach for the capability analysis based on measurement system analysis: a case study for coal quality detection equipment. (2016) - Yuan, Qinghe; Yin, Xianhui; Yan, Wei; Tan, Yanyan; Li, Zhaojun
In order to ensure the accuracy and precision of equipment of coal quality detection, analyse the causes, and update the inaccurate equipment to avoid the losses and wastes, the existing methods and its defects are analysed. The feasibility and limitations of applying measurement system analysis to solve the problem is also studied. The difficulties of experiment about MSA for coal quality are resolved by defining the range of the same batch of coal products, designing different sample levels and studying the method of achieving multiple measurements with single sample in destructive test. Meanwhile, three indexes including repeatability and reproducibility (R&R), percentage variation and number of distinct categories are used to evaluate the equipment capability. Based on the actual production of coal preparation, the method is applied in detail. The application result shows that the method can provide an effective evaluation for the capability of coal quality detection equipment during the production.